INTEGRATED PLATFORMS FOR AUTOMATING PERSONAL FINANCIAL ACCOUNTING BASED ON CHATBOTS AND CLOUD TECHNOLOGIES - Haitan, О. M.; Snytkа, I. V. (Systems and Technologies, 2025)
In the context of increasing financial complexity and the growing need for better personal finance management, virtual personal financial assistants have emerged as essential tools for individuals seeking efficient ways to track, manage, and analyze their finances. The widespread adoption of smartphones and cloud-based technologies has contributed to the growth of automated financial solutions that assist users in budgeting, expense tracking, and making financial decisions. This study examines the conceptual and practical foundations of developing a virtual personal financial assistant based on Telegram chatbot technology, integrated with cloud services such as Google Sheets. The research explores methods for automating financial accounting, enhancing user interaction with financial data, and ensuring secure, scalable, and accessible financial accounting tool for individual and family.The paper investigates the integration of asynchronous communication models using Aiogram, implementation of cloud- based data management via the Google Sheets API, and the use of a lightweight database SQLite for handling service-related data. Particular attention is given to the interaction logic, user experience design, and security protocols based on OAuth2 for managing sensitive financial data.Furthermore, the research analyzes the user experience, focusing on how the system supports both individual and shared financial management. It explores the functionality that enables multiple users to collaboratively manage a family budget.The proposed solution represents an approach, combining elements of software engineering, cloud computing, and digital finance. The study highlights the advantages of chatbot-driven interfaces for personal finance management and outlines the potential for future enhancements, including greater automation, multi-user collaboration, and artificial intelligence integration.